From velocity and attenuation tomography to rock physical modeling: Inferences on fluid‐driven earthquake processes at the Irpinia fault system in southern Italy. Issue 13 (15th July 2017) - Amoroso, O.; Russo, G.; De Landro, G.; Zollo, A.; Garambois, S.; Mazzoli, S.; Parente, M.; Virieux, J.
Abstract: We retrieve 3‐D attenuation images of the crustal volume embedding the fault system associated with the destructive M s 6.9, 1980 Irpinia earthquake by tomographic inversion of t * measurements. A high Q P anomaly is found to be correlated with the 1980 fault geometry, while the Q S model shows regional‐scale variations related to the NE edge of the uplifted pre‐Tertiary limestone. An upscaling strategy is used to infer rock properties such as porosity, consolidation, type of fluid mixing, and relative saturation percentage at 8–10 km fault depth. We constrain the porosity and consolidation in the ranges 4–5% and 5–9, respectively, with the possible fluid mixes being both brine‐CO2 and CH4 ‐CO2 . The consolidation parameter range indicates high pore pressures at the same depths. These results support the evidence for a fracture system, highly saturated in gases and a seismicity triggering mechanism at the fault zone, which is strongly controlled by fluid‐induced pore pressure changes. Key Points: Three‐dimensional attenuation images and rock properties of the crustal volume embedding the fault system associated with the destructive Ms 6.9, 1980 Irpinia earthquake Evidence for a fractured and fluid‐saturated medium, with the presence of brine‐CO2 and CH4 ‐CO2 Pore pressure increase is the dominant mechanisms triggering and controlling the microseismicity